Study of bollard pull harbour tug: focuses on stability and straight movement - Md Palil, Md Dan; Khairul Azahar, Khairul Fikhri (Penerbit Universiti Teknikal Malaysia Melaka, 2012)
Method of design and analysis of bollard pull harbour tug focuses in its stability and straight movement. Research includes a brief review of general description of bollard pull harbour tug, tug boat functions, tug boat characteristics, functions, operation modes, requirements for tug boats, stability standard and factor affecting stability, stability requirements, displacement and buoyancy, fundamental of design and a very last, fundamental of analysis. This research also discuss about the methodology to implement the design and analysis to measure the stability and movement of the tug boat. The purpose of design modelling is to identify the error of the existing design and to redesign to eliminate or reduce errors. The error consists of the hull structure and skeg design. However to redesign the hull and skeg must be done during design stage. For this report, it will discuss only the basis of the design methodology. The analysis of the stability and straight movement of the bollard pull harbour tug are using software analysis. SolidWorks and ANSYS are the proposed analysis software that will implement for this thesis. The analysis of the tug boat is study on static and dynamic analysis that discuss about finite element analysis and hydrodynamic analysis. Dynamic analysis is important part because it deals with how the tug boat moving in a stable and balanced during its operation.